siRNA modified with 2′-deoxy-2′-c-methylpyrimidine nucleosides - Dellafiore, María Andrea (2018)
(2′S)-2′-Deoxy-2′-C-methyluridine and (2′R)-2′-deoxy-2′-C-meth-yluridine were incorporated in the 3’-overhang region of the sense and antisense strands and in positions 2 and 5 of the seed region of siRNA duplexes directed against Renilla luciferase, whereas (2′S)-2′-deoxy-2′-C-methylcytidine was incorporated in the 6-position of the seed region of the same constructions. A dual luciferase reporter assay in transfected HeLa cells was used as a model system to measure the IC50 values of 24 different modified duplexes. The best results were obtained by the substitution of one thymidine unit in the antisense 3’-overhang region by (2′S)-or (2′R)-2′-deoxy-2′-C-methyluridine, reducing IC50 to half of the value observed for the natural control. The selectivity of the modified siRNA was measured, it being found that modifications in positions 5 and 6 of the seed region had a positive effect on the ON/OFF activity.